Cellular total lipid peroxidation, and glutathione S transferase levels in larvae and pupae of Aedes Aegypti with catalysts preparation of Mg-doped tio2 nanoparticles - AlSalih, Moatasem; Samsudin, Syakirah; Arshad, Siti Suri (IOP Publishing, 2021)
Aim: synthesis, characterization, and application of modifying nanocomposite TiO2 doped with Magnesium for photodegradation of antioxidant system Larvae and Pupae of Aedes Aegypti Catalysts Preparation of Mg-doped TiO2 to determine activity of oxidative stress (MDA) and glutathione S Transferase, were known as a parameter of defense system resistance and immune maintained. This study was undertaken to assess the potential role of growth of stages of Aedes Aegypti correspondence with oxidant and antioxidant balance triggered by nanoparticle exposure. The amounts of these parameters in cellular samples were investigated using the following materials and procedures, intake 100 larvae and 100 pupae as subjects with (study subjects) and 3-9 days' age-matched with healthy subjects as controls. at the second of the admission, as a marker of lipid peroxidation, and therefore an indicator of the activity of standard free radicals Nanoparticles Photo Catalysts, TiO2 doped with Mg, the standard prepared Nanopowder changes from the forbidden band TiO2 standard doping with atoms of Mg ،Mg) using the sol-gel method, for Mg-doped TiO2 nanoparticles, the estimated band gap energy is 2.92 eV. Tissue MDA was used to estimate thiobarbituric acid reactive substances (TBARS), and liquid glutathione reductase activity was assessed using Goldberg DM's method. Results: When compared to controls, there was a dramatic rise in MDA content and glutathione s transferase efficiency in larvae and pupae populations exposed to photo catalyst modified nanoparticles. Conclusion: Increased MDA support to oxidative stress in larvae and pupae samples supports enhanced oxygen-free radical generation, as indicated by our findings. Increased antioxidant enzyme activity could be a compensatory mechanism in response to increased oxidative stress. The findings point to glutathione s transferase's antioxidant activity in response to increasing oxidative stress in the treated group.